2014
DOI: 10.3390/ijerph110706940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Seasonal Climate Variability and Age-Specific Mortality in Northern Sweden before the Onset of Industrialization

Abstract: Background and aims: Little is known about health impacts of climate in pre-industrial societies. We used historical data to investigate the association of temperature and precipitation with total and age-specific mortality in Skellefteå, northern Sweden, between 1749 and 1859. Methods: We retrieved digitized aggregated population data of the Skellefteå parish, and monthly temperature and precipitation measures. A generalized linear model was established for year to year variability in deaths by annual and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…As a proxy for Skellefteå weather, we used monthly data on precipitation and temperature from Umeå, a town 110 kilometres south of Skellefteå. For the period 1800-1859, early temperature recordings from Uppsala (roughly 600 kilometres south) and from Tornedalen (roughly 230 kilometres north) were used for the reconstruction of Umeå monthly temperature (see details in Rocklöv et al 2014). Weather data was obtained from the Swedish Meteorological and Hydrological Institute (SMHI), with the exception of Tornedalen data, which was taken from Klingbjer and Moberg (2003).…”
Section: Climate Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As a proxy for Skellefteå weather, we used monthly data on precipitation and temperature from Umeå, a town 110 kilometres south of Skellefteå. For the period 1800-1859, early temperature recordings from Uppsala (roughly 600 kilometres south) and from Tornedalen (roughly 230 kilometres north) were used for the reconstruction of Umeå monthly temperature (see details in Rocklöv et al 2014). Weather data was obtained from the Swedish Meteorological and Hydrological Institute (SMHI), with the exception of Tornedalen data, which was taken from Klingbjer and Moberg (2003).…”
Section: Climate Datamentioning
confidence: 99%
“…According to our earlier research, in Sweden between 1749 and 1859 annual average temperature and precipitation had little impact on annual death counts. But while higher springtime temperatures and precipitation decreased annual mortality, high levels of rain in autumn led to higher annual mortality (Rocklöv et al 2014;Schumann et al 2013). There was also evidence that older children were most vulnerable to an unfavourable climate, while there was a less pronounced impact on infants .…”
Section: Introductionmentioning
confidence: 99%
“…For the proximity to wetlands variable, we estimate separate models for three high-risk groups: infants, children aged 1-5, and females aged 20-50 (WHO 2015). For the population density, we select children aged 1-15 who are sensitive to environmental factors (cf., e.g., Bengtsson 1999;Rocklov et al 2014). Separate models are estimated for the geocoding levels as well as for the different methods applied to the geographic context variables.…”
Section: Survival Analysismentioning
confidence: 99%
“…Consequently, the differences in productivity changed from being regional to local in line with the enclosures. Finally, the effect of climate on mortality in preindustrial societies has been studied by combining microlevel and macrolevel data (Bengtsson and Broström 2010;Rocklov et al 2014;Schumann et al 2013). For example, Schumann et al (2013), using parish-level data, found that for a rural region in northern Sweden in the 18 th and 19 th century, a high amount of autumn rain increased the total number of deaths for all age groups.…”
Section: Previous Researchmentioning
confidence: 99%
“…Children aged 1-15 are studied because they were sensitive to malnutrition as well as to environmental factors (Bengtsson 1999;Rocklov et al 2014;Schumann et al 2013;Wolleswinkel-van den Bosch et al 2000) and the regional differences in mortality were usually larger among them (Van Poppel, Jonker, and Mandemakers 2005). As a sensitivity test, we also analyse infants (age 0-1) to compare the two age groups.…”
Section: Introductionmentioning
confidence: 99%